Effects of kaffir lime peel extract and ginger extract on the postharvest quality of tomato - Nurul Faziha Ibrahim,; NurFazleen Syuhada Rostam,; Nor Amira Izati Nor Azman,; Shamsul Bahri Abdul Razak, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Harvested tomatoes are very sensitive to changing environments and rough handling techniques. This practice becomes a major challenge to the sellers either for fresh market or long-distance market to maintain the quality and prolong its shelf life. Fungal disease and mechanical injuries due to improper handling practice will deteriorate the fruits, thus reducing the customer’s acceptability and its market value. This study was aimed to provide a low-cost technique by evaluating the potential of aqueous kaffir lime peel extract (KLE) and aqueous ginger extract (GG) in maintaining the quality of tomatoes. For this purpose, healthy tomatoes at stage 5 were dipped in 20% GG, 25% KLE and 50% KLE before incubated at room temperature. The data on postharvest parameters namely weight loss, firmness, total soluble solids (TSS), and lycopene content were recorded at two days intervals. The results show that 25% KLE and 50% KLE recorded a good promising agent to maintain the quality of tomatoes. Also, treatment of tomatoes with 50% KLE can significantly preserve the weight, firmness, TSS, and lycopene content of the fruits. None of the tomatoes treated with 20% GG showed significant results in this study. The output of this study will provide important information on the potential of KLE and GG in prolonging the shelf life of tomatoes.